Dimension and stackability of cassava (Manihot esculanta Crantz) chips for mass production - Ismail, N. A.; Mohd Adzahan, Noranizan; Shamsudin, Rosnah; Karim, Roselina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Cassava chips that exist in the current market have no standardisation and cannot be stacked nicely into cylindrical container. The objectives of this work are to determine the different dimension of cassava chips produced with different thickness and to develop stackable chips during mass production. Fresh cassava tubers were harvested, washed, peeled and sliced. The thickness measurements used were 1.0 mm, 1.5 mm, 1.75 mm and 2.0 mm and 1.27 mm thickness was measured from commercial potato chips as a controlled sample. Then, it was fried in deep fat fryer with the temperature of 170°C. For each thickness studied, different numbers of slice (10, 20, 30 and 40 slices) were fried simultaneously. Results showed that there are 6 shapes of fried chips produced during the frying. To conclude, thickness of the slice and number of slices fried simultaneously give impact towards the shape of fried chip.